Meghdoot App to support the digitalization of agroadvisories in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
MEGHDOOT carries agro-meteorology advisories for all the 717 districts of India. The app has been downloaded about 53 000 times with active users almost 20k as on Feb 2020. Cumulatively, the MEGHDOOT app has disseminated about 145k advisories since its launch in July 2019. ( https://play.google.com/store/apps/details?id=com.aas.meghdoot)